4‐O‐methylascochlorin activates autophagy by activating AMPK and suppressing c‐Myc in glioblastoma. Issue 10 (20th June 2020) - Hwang, Soon‐Kyung; Han, Si‐Yoon; Jeong, Yun‐Jeong; Magae, Junji; Bae, Young‐Seuk; Chang, Young‐Chae
Abstract: A prior study identified that 4‐ O ‐methylascochlorin (MAC), a methylated derivative of ascochlorin (ASC) from the fungus Ascochyta viciae, activates autophagy in leukemia cells by suppressing c‐Myc phosphorylation. However, the effects of MAC on autophagy in other cancer cells remain unknown. In the present study, we demonstrated that MAC activated autophagy in human glioblastoma. MAC increased expression of autophagy‐related proteins, such as LC3‐II and Beclin‐1. Moreover, MAC stimulated AMP‐activated protein kinase (AMPK) phosphorylation and suppressed phosphorylation of the mTOR, p70S6K, and 4EBP1. The well‐known AMPK activator metformin increased LC3‐II levels, which were augmented by MAC cotreatment. AMPK knockdown decreased LC3‐II levels and inhibited MAC activation of autophagy. Furthermore, MAC suppression of c‐Myc expression activated autophagy. Treatment with the c‐MYC inhibitor, 10058‐FA, induced autophagy, as did c‐Myc small interfering RNA knockdown. These effects were augmented by MAC cotreatment. Taken together, these findings indicated that MAC induces autophagy in human glioblastoma by activating AMPK signaling and inhibiting c‐Myc protein expression in human glioblastoma.